A system for deduction-based formal verification of workflow-oriented software models - Klimek, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
The work concerns formal verification of workflow-oriented software models using the deductive approach. The formal correctness of a model`s behaviour is considered. Manually building logical specifications, which are regarded as a set of temporal logic formulas, seems to be a significant obstacle for an inexperienced user when applying the deductive approach.
Keywords: formal verification; deductive reasoning; temporal logic; semantic tableaux; workflow patterns; logical primitives; generating logical specifications; business models; BPMN